2014
DOI: 10.2478/s11658-014-0183-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel estradiol analogue induces apoptosis and autophagy in esophageal carcinoma cells

Abstract: Abstract:Cancer is the second leading cause of death in South Africa. The critical role that microtubules play in cell division makes them an ideal target for the development of chemotherapeutic drugs that prevent the hyperproliferation of cancer cells. The new in silico-designed estradiol analogue 2-ethyl-3-Osulfamoyl-estra-1,3,5(10)16-tetraene (ESE-16) was investigated in terms of its in vitro antiproliferative effects on the esophageal carcinoma SNO cell line at a concentration of 0.18 µM and an exposure ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…This observation is supported by a study where 17β estradiol analog-treated MDA-MB-231, MCF-7 and MCF-12A cells demonstrated the presence of apoptotic bodies and vacuoles [63]. Fragmented nuclei and apoptotic bodies were detected within tumorigenic cells that were exposed to combination compounds, which indicate late stages of apoptosis and also support previous cell cycle- and apoptotic quantification [28,62]. …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This observation is supported by a study where 17β estradiol analog-treated MDA-MB-231, MCF-7 and MCF-12A cells demonstrated the presence of apoptotic bodies and vacuoles [63]. Fragmented nuclei and apoptotic bodies were detected within tumorigenic cells that were exposed to combination compounds, which indicate late stages of apoptosis and also support previous cell cycle- and apoptotic quantification [28,62]. …”
Section: Discussionsupporting
confidence: 70%
“…Cells that divided in the presence of the C9+DCA treatment proceeded from being arrested at the mitotic phase to forming multiple micronuclei and apoptotic bodies. Other studies recently conducted also showed similar results where a sulphamoylated antimitotic compound-treated MCF-7, and/or MDA-MB-231 or esophageal carcinoma cells (SNO) cells showed a decrease in cell density along with morphological indicators of apoptosis [8,28,62]. Distorted cell shape, high density of digit-like apical microvilli, formations of vacuoles, lysosomes and apoptotic bodies, heterochromatin, as well as fragmented DNA were detected in both cell lines by means of transmission electron microscopy.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies suggested that ESE-16 exposure in certain cancer cell lines leads to increased autophagy [2, 9, 10]. This conclusion was drawn from MDC staining of cells and autophagy-regulating protease 4A (Atg 4A) expression levels (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Here, we set out to obtain conclusive data to allow us to identify the origin of the vesicles formed after ESE-16 exposure. First, we compared vesicle size and distribution using MDC staining between cells exposed to ESE-16 and cells exposed to the known autophagy inducer tamoxifen [9, 10]. Our data shows that tamoxifen does indeed induce the propagation of distinct, bright MDC-positive foci.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge this has not been further developed. Another generally related sulfamoylated steroid derived from this background work, ESE-16, has been more recently proposed [51] and shown to cause both apoptotic and autophagic cell death [52].…”
Section: Emate and E2mate Derivativesmentioning
confidence: 99%